Idiostyle Specificity and the Image of the Author in the Works of L.S. Petrushevskaya (Eurasian Journal of Humanities and Social Sciences, 2022)
The article is devoted to the issues of scientific interpretations of the term " individual style". Various interpretations of the concept are presented, a brief overview of the individual style . Special attention is paid to the work of L.S.Petrushevskaya. The article is relevant due to the fact that the scientific interpretation of the concept is determined using old Soviet-era cliches. The novelty of this article lies in the study of the term " individual style" in the works of L.S.Petrushevskaya from new angles.